Adalimumab versus ustekinumab as first-line biological in moderate-to-severe Crohn's disease: real-life cohort from a tertiary referral center. Issue 10 (30th August 2022) - Moens, Annick; Alsoud, Dahham; Verstockt, Bram; Sabino, João; Ferrante, Marc; Vermeire, Séverine
Abstract : Background: Therapeutic options for Crohn's disease are growing, making the choice of first-line therapy relevant. Both adalimumab and ustekinumab are effective in moderate-to-severe Crohn's disease. The Safety and Efficacy of Adalimumab Versus Ustekinumab for One Year trial suggested no difference in clinical or endoscopic remission at week 52 in biological-naive Crohn's disease patients. We explored if results withstand in the real world. Methods: We included bio-naive Crohn's disease patients starting adalimumab or ustekinumab between 2017 and 2020. Patients had endoscopy-proven moderate-to-severe disease [Simple Endoscopic Score for Crohn's disease (SES-CD) ≥3]. Clinical remission was defined as Harvey Bradshaw Index (HBI) <5 or physician global assessment. Endoscopic remission (SES-CD <3) and improvement (≥50% reduction in SES-CD from baseline) were assessed at W26-52. Propensity score matching was used. Results: A total of 68 biological-naive Crohn's disease patients were included (32 adalimumab and 32 ustekinumab) and followed for median of (IQR) 60 (33–104) weeks. Patients had significantly higher odds of achieving endoscopic remission with adalimumab than ustekinumab [adjusted odds ratio (aOR), 2.73; confidence interval (CI), 1.12–7.36; P = 0.03]. Also, more adalimumab-treated patients achieved endoscopic response, clinical remission at week 26 and 52 (aOR, 2.24; CI, 0.94–5.71; P = 0.07; aOR, 1.26; CI, 0.36–4.51; P = 0.72; aOR, 1.58; CI, 0.54–4.88; P = 0.41, respectively). Treatment persistence was not different between groups (P = 0.44). The number of adverse events was similar. Conclusion: In a real-world cohort of biological-naive Crohn's disease patients, adalimumab was superior to ustekinumab in achieving endoscopic remission. No differences in clinical remission at W26-52 or treatment persistence were observed. Both adalimumab and ustekinumab remain good options as first-line biologicals in moderate-to-severe Crohn's disease.